Enhancing Eighth-Grade Students' Vocabulary Mastery Through The Simpler Digital Application - Genta Juanda (Universitas Samudra, 2026)
This study investigated the effect of the Simpler application on the vocabulary mastery of eighth-grade students at SMP Negeri 1 Simpang Jernih. Vocabulary mastery is a basic component of English learning because it supports listening, speaking, reading, and writing. Preliminary observation showed that students had limited vocabulary knowledge and often relied on teacher translation. To respond to this classroom problem, the Simpler application was used as a digital learning medium that offers vocabulary exercises, repetition, contextual examples, and interactive tasks. This research employed a quantitative approach with a pre-experimental one-group pre-test and post-test design. The participants were 23 eighth-grade students selected through purposive sampling. The treatment was conducted in five learning sessions, and the students completed a 20-item vocabulary test before and after the treatment. The data were analyzed using descriptive statistics, a paired sample t-test, and effect-size interpretation. The results showed that the mean score increased from 32.61 in the pre-test to 45.87 in the post-test, with a mean gain of 13.26 points. The obtained t-value was 6.247, which was higher than the t-table value of 2.074 at the 5% significance level. The effect size was also large, which indicates that the improvement was meaningful in this classroom context. These findings suggest that the Simpler application can support vocabulary learning when it is used with clear teacher guidance, repeated practice, and collaborative activities. However, the findings should be interpreted carefully because the study used one class only and did not involve a control group.